Khalid Javed’s Novel Writing in Modern Context - Atish, Hina; Khan Kalyani, Mumtaz (sourcecoder, 2022)
Khalid javed,s art is in fact the name of human experience and awareness of observation. Khalid javed,s novels are the best interpreters of the storm of suffering, misery, sorrow and loneliness that the human race has endured. His thought in the universe is as if the interpretation of reality and reality is constant possibility the mysticism of understanding life and understanding the facts has ignited the process if playing openly with in the extinct boundaries of his art-Khalid javed,s ruthless statement leaving all the ends of the story so loose and confusing that it becomes a challenge for the reader to understand-the theme of all three of Khalid javed,s novels is death-your novels of philosophical and psychological issues as well as social, political, Cultural and economic life is also a charisma.